An Analysis Of Minimal Pairs Of Consonant Sounds In English - Asmaul Husna; Siti Sholikhah; Yani Lubis (Universitas Palangka Raya, 2023)
This study aims to analyze minimal pairs of consonant sounds in English and explore their significance in language learning and teaching pronunciation. Minimal pairs are two words that differ only in one consonant sound, and this analysis aims to provide an understanding of the important role of minimal pairs in developing phonological awareness and improving pronunciation accuracy in English.This research involved identifying and analyzing minimal pairs of consonant sounds in English, including consonant sounds such as /p/ and /b/, /s/ and /z/, and /t/ and /d/. This analysis includes examining the articulation differences and acoustic characteristics of each minimal pair, with the aim of helping English learners understand the subtle phonetic differences between these consonant sounds. Through a deep understanding of minimal pairs, learners can develop their ability to distinguish and produce consonant sounds more accurately.In addition, this study also reviews the pedagogical implications of using minimal pairs in learning English pronunciation. Activities that involve minimal pairs, such as exercises on understanding and producing consonant sounds, can help learners increase their sensitivity to the different sounds in English. By engaging students in minimal pair practice, teachers can help them improve their pronunciation and increase their clarity of communication in English.